2007
DOI: 10.1177/08857288070300030501
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Improving Career Services for Postsecondary Students With Disabilities

Abstract: Improved career services in postsecondary education are needed if students with disabilities are to experience greater success in acquiring and maintaining employment following college graduation. In this study, postsecondary students with disabilities, faculty members, and student personnel professionals responded to results from a student survey that identified the strengths and weaknesses in career services at colleges and universities. In a series of focus groups, these stakeholders recommended 114 specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…College students with disabilities are afforded protections under multiple pieces of legislation including the Americans with Disabilities Act (ADA) and Section 504 of the Rehabilitation Act of 1973 (Mowbray et al, 2006; Roessler, Hennessey, & Rumrill, 2007). Legislation requires that colleges and universities provide reasonable accommodations to qualified students with disabilities.…”
Section: Meeting the Needs Of College Students With Disabilitiesmentioning
confidence: 99%
“…College students with disabilities are afforded protections under multiple pieces of legislation including the Americans with Disabilities Act (ADA) and Section 504 of the Rehabilitation Act of 1973 (Mowbray et al, 2006; Roessler, Hennessey, & Rumrill, 2007). Legislation requires that colleges and universities provide reasonable accommodations to qualified students with disabilities.…”
Section: Meeting the Needs Of College Students With Disabilitiesmentioning
confidence: 99%
“…Similarly, SWD in a training program reported that self-advocacy skills are important for their transition to STEM majors and careers (Izzo et al, 2011). Roessler et al (2007) recommended college career services to provide formal self-advocacy training programs for SWD to gain disability employment knowledge, develop strategies to request reasonable accommodations, and infuse self-advocacy into daily activities.…”
Section: Resultsmentioning
confidence: 99%
“…More integration between college career services and student disability services is crucial to providing SWD with career supports that are more tailored to their unique needs. Collaboration between professionals in disability services and career services, government agencies (e.g., State-Federal Vocational Rehabilitation Services), and other key stakeholders is needed (Aune & Kroeger, 1997; Mask & DePountis, 2018; Roessler et al, 2007). Student disability services play a vital role in SWD’s college adjustment and academic achievement (Chiu et al, 2019) as it is a primary source for SWD to request academic accommodations and other support services.…”
Section: Implications For Practicementioning
confidence: 99%
“…Despite the mandate to schools to provide reasonable accommodations stated in both Section 504 of the Rehabilitation Act and in the Americans with Disabilities Act, limited resources and lack of specific guidelines has led to wide variations in the types of supports available on college campuses for vocational rehabilitation consumers with disabilities (Sharpe, Johnson, Izzo, & Murray, 2005). This potentially impacts the level of educational engagement, program completion rates, and future employment for students with disabilities (Roessler, Hennessey, & Rumrill, 2007). Collaboration between college disability coordinators, rehabilitation providers, and secondary schools is crucial for the successful employment of college students with disabilities (Lindstrom, Flannery, Benz, Olszewksi, & Slovic, 2009).…”
Section: Discussionmentioning
confidence: 99%